Heaven help us : how faith communities inspire hope, strengthen neighborhoods, and build the future - Kasich, John; Paisner, Daniel (Zondervan Books, 2025)
Heaven Help Us by John Kasich explores the role of faith-based communities and individuals in addressing social challenges across the United States. Drawing from a variety of real-life examples -- including a Greek Orthodox network of group homes for individuals with autism, an Islamic center promoting interfaith dialogue, and a church-based immigration support program -- Kasich highlights the impact that religious institutions can have in local communities. As both a former governor and a person of faith, Kasich presents his perspective on how religious organizations contribute to civic life. The book includes narratives of individuals inspired by their faith to lead community-focused initiatives, analysis of what makes some faith institutions particularly effective, and suggestions for how others might engage in similar efforts. Rather than focusing solely on political or theological arguments, Heaven Help Us offers practical insights and stories meant to illustrate the positive influence of religious institutions in civic engagement and community development.